Thromboelastography and Rotational Thromboelastometry for the Surgical Intensivist: A Narrative Review - Drumheller, Byron C. (J Trauma Acute Care Surg, 2019)
BACKGROUND: Viscoelastic tests (VETs), specifically thromboelastography (TEG) and rotational thromboelastometry (ROTEM), are gaining popularity in the management of critically ill surgical patients with hemorrhage or thrombosis due to their comprehensive characterization of the coagulation process and point-of-care availability in comparison to conventional coagulation tests (CCTs). We review current evidence for VET use in patients in the surgical intensive care unit (SICU). METHODS: We searched PUBMED, EMBASE and the Cochrane Library through May 30, 2018 for articles that evaluated the use of VETs in patient populations and clinical scenarios germane to the surgical intensivist. Individual articles were critically evaluated for relevance and appropriate methodology using a structured technique. Information on patient characteristics, timing and methods of CCTs/VETs, and outcomes was collected and summarized in narrative form. RESULTS: Of 2,589 identified articles, 36 were included. Five (14%) were interventional studies and 31 (86%) were observational. Twenty-five (69%) evaluated TEG, 11 (31%) ROTEM and 18 (50%) CCTs. Investigated outcomes included quantitative blood loss (13 (36%)), blood product transfusion (9 (25%)), thromboembolic events (9 (25%)) and mortality (6 (17%)). We identified 12 clinical scenarios with sufficient available evidence, much of which was of limited quantity and poor methodological quality. Nonetheless, research supports the use of VETs for guiding early blood product administration in severe traumatic hemorrhage and for the prediction of excess bleeding following routine cardiac surgery. In contrast, evidence suggests VET-based heparin dosing strategies for venous thromboembolism prophylaxis are not superior to standard dosing in SICU patients. CONCLUSIONS: While VETs have the potential to impact the care of critically ill surgical patients in many ways, current evidence for their use is limited, mainly because of poor methodological quality of most available studies. Further high-quality research, including several ongoing randomized controlled trials, is needed to elucidate the role of TEG/ROTEM in the SICU population.